X-ray emission from supernova shock waves - Nymark, Tanja (Stockholms universitet, Institutionen för astronomi, 2007)
A theoretical study of the interaction between supernovae and their surroundings is presented. Supernovae are the endpoint of the life of massive stars, and are the dominant contributors to the chemical evolution of the Universe. During its life a massive star greatly modifies its environment. During and after the explosion of the star it interacts with its surroundings in a number of ways. A study of this interaction yields invaluable information about the late stages of stellar evolution and the physics of supernova explosions. Recent advances in observational facilities have given a wealth of observational data on interacting supernovae, and it is therefore essential to have good theoretical models for interpreting the data. This thesis presents an overview of the physics of supernovae and of their interaction with a circumstellar medium. In particular the reverse shock created by the interaction is investigated. In most Type IIL and Type IIn supernovae this shock is radiative, and due to the high temperature most of the radiation comes out as X-rays. A numerical model is presented which calculates the emission from the cooling region behind the reverse shock in a self-consistent way, by combining a hydrodynamic model with a time-dependent ionization balance and multilevel calculations. This has been applied to some of the best cases of circumstellar interaction. As a further application of the model the radio and X-ray emission from Type IIP supernovae is discussed. We estimate the mass loss rate of the progenitors of Type IIP supernovae, and find that a superwind phase is not required. VLT observations of the ring of SN 1987A show broad optical emission lines coming from a range of ionization stages, in particular optical coronal lines of Fe X-XIV. Models of the line emission indicate that the lines are formed by cooling shocks with shock velocities in the range 310-390 km/s, confirming the picture of shocks striking the protrusions from the ring obliquely. X-ray observations of the Type IIb SN 1993J and Type IIn SN 1998S are analyzed. For SN 1993J we find that the spectrum is best fit with a CNO-enriched composition. For SN 1998S we find that the high metal overabundance that has previously been claimed, is not necessary when a self-consistent model of the cooling region is applied.